Beyond bricks and mortar: a qualitative examination of factors influencing diffusion of an innovative PETE graduate program - Jones, Emily; Eberline, Andrew; Knipe, Robert (Curriculum Studies in Health and Physical Education, 2020)
As novel approaches to post-graduate education emerge and professional learning concepts evolve, there is a need for additional research investigating the processes by which physical education teacher education (PETE) faculty and administrators conceptualise and launch non-traditional graduate programming. The purpose of this study was to investigate stakeholders’ perceptions of the factors influencing the diffusion of a one-year, contextually based, full-immersion master’s degree in PE. Six stakeholders, including individuals from a mid-sized university, a global fitness corporation, and a rural K-12 school district all located within the United States, participated in semi-structured interviews. Deductive content analysis methods were used to analyse the data. Utilising Roger’s Attributes of Innovation, eleven sub-themes emerged. Findings represent stakeholders’ perceptions of facilitators and barriers to the implementation and diffusion of an innovative effort to deliver graduate education. Challenges and lessons learned provide insight for PETE faculty and administrators seeking to expand graduate education beyond bricks and mortar.
_eprint: https://doi.org/10.1080/25742981.2020.1719853
Keywords: Physical education teacher education; collaboration; dept.hms; graduate education; innovation; peer-reviewed; practice-to-theory

What the HETE/PETE? - Benes, Sarah; McMullen, Jaimie; Seymour, Clancy; Jones, Emily; Cardina, Catherine; Ramsey, Victor; Centeio, Erin (Journal of Physical Education, Recreation & Dance, 2023)
The K-12 health and physical education professions are largely guided and supported by three entities. They include state departments of education, national and state professional associations, and teacher education programs (i.e., health education teacher education [HETE] and physical education teacher education [PETE]). From the outside looking in, it may seem that HETE and PETE programs are not dissimilar, yet both disciplines continue to operate largely within individual vacuums, each being historically undermined and marginalized. Therefore, questions regarding the purpose and relevance of K-12 health and physical education programs are continually raised. These common challenges may have a negative impact on recruitment of health and physical education teachers, retention of HETE and PETE programs, and ultimately the learning outcomes of youth in schools. In this article, we review critical challenges faced by both HETE and PETE programs with the hope that this can lead to collaboration, advocacy, and meaningful change.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/07303084.2023.2221610
Keywords: dept.hms; peer-reviewed